THE CONCEPT OF ONLINE BUYING IN SHARIAH ECONOMY - Abdul Hadi Ismail; Riyan Pradesyah (Proceeding International Seminar of Islamic Studies, 2022)
Buying and selling is an activity that is often carried out by humans, where currently buying and selling has undergone a model development. Previously, buying and selling had to meet directly between the seller and the buyer, but at this time buying and selling can be done virtual or online. This is what is now in the public spotlight, where a lot of fraud is carried out on the results of buying and selling online, there are many cases that occur, such as the difference between the goods in the online store and the fact that the ordered goods do not arrive, the ordered goods are defective and so on. The research method in this article uses a literature review, where researchers look for sources related to the concept of buying and selling, then describe them and narrate them in research principles. The results obtained, that everyone wants the renewal of the activities carried out, including buying and selling. In Islamic Economics, the concept of buying and selling online can be used, it just has to comply with the sharia that has been regulated, upholding honesty, goods sold are not forbidden in Islam, there is a willingness between the seller and the buyer, and trustworthiness. This is what must be applied in online buying and selling activities according to the perspective of Islamic economics.Keywords: Shariah Economics, Buying and Selling Online